Upaya Meningkatkan Hasil Belajar Passing Bawah Bolavoli Melalui Penerapan Model Pembelajaran Student Teams Achievement Divisions (STAD) Pada Siswa Kelas IV di SDN Sidomulyo Kec. Semen - Mohammad Agung Pratama; Reo Prasetiyo Herpandika; Rina Agus Pambudi (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this study was to improve the learning outcomes of volleyball underhand passing by applying the STAD learning model to Grade IV Students of SDN Sidomulyo, Semen District. This study is a Classroom Action Research (CAR). This study was conducted in two cycles, consisting of four stages in each cycle consisting of planning, action implementation, observation, and reflection. The subjects of the study were Grade IV Students of SDN Sidomulyo, Semen District, totaling 24 students consisting of 13 male students and 11 female students. Data collection techniques were tests and observations. The results of data analysis in cycle I showed that student learning outcomes increased, the learning outcomes of volleyball underhand passing were 23 students (96%) who successfully achieved the KKM in the knowledge aspect. In Cycle I of learning volleyball underhand passing in the social and spiritual attitude aspect, there were 2 students (8%) who received the Very Good category, 19 students (79%) received the Good category, and 3 students (13%) received the Sufficient category. In Cycle I of volleyball underhand passing learning, the aspect of volleyball underhand passing skills, there were 9 students (38%) who successfully achieved KKM and 15 students (62%) who had not achieved KKM. In Cycle II, learning outcomes increased again compared to Cycle I in volleyball underhand passing learning, there were 24 students (100%) who successfully achieved KKM in the knowledge aspect. In Cycle II of volleyball underhand passing learning, the aspect of social and spiritual attitudes, there were 5 students (12%) who received the Very Good (A)category, there were 19 students (88%) who received the Good (B) category. In Cycle II of volleyball underhand passing learning, the aspect of volleyball underhand passing skills, there were 19 students (88%) who successfully achieved KKM and 4 students (12%) who had not achieved KKM. Based on the data analysis that has been carried out and described in CHAPTER IV, it can be concluded that the application of the STAD learning model in learning can improve volleyball underhand passing learning outcomes in Grade IV Students of SDN Sidomulyo, Semen District.